Politics and feminism: An introduction - Arneil, Barbara (Blackwell, 1999)
This book addresses the question of gender and feminism in western political theory and practise. It provides students with both the theoretical and historical underpinnings of women's exclusion from politics, and the feminist response to this exclusion.
Keywords: amériques; approches et analyses; cours; discipline; discriminations; europe; fem1000; histoire et politique; inégalités; occident; premier cycle; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; théories politiques

L'action politique féministe et le défi postmoderne - Bernard, Annie (Université du Québec à Montréal, 1998)
Keywords: IREF; approches et analyses; discipline; militance; mémoires/thèses; postmodernisme; science politique; science politique et droit; thématiques

Le genre : assez fort pour lui, mais conçu pour elle - Garneau, Édith (Politique et Sociétés, 1998)
Cet article vise à examiner la manière dont certaines théoriciennes féministes américaines, anglo-saxonnes, françaises et québécoises ont conceptualisé les concepts ambigus de sexe et de genre. Il présente les idées nouvelles et complexes de Joan Scott, Seyla Benhabib et Iris Marion Young et a pour but de permettre et de faire valoir d’autres façons pour les politologues et les féministes de conceptualiser le genre.
Keywords: 1900-1999; cours; discipline; fem1000; genre; identités LGBTQIA2+; occident; premier cycle; périodes historiques; ressource en ligne; science politique; science politique et droit; thématiques

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Section: xi, 365 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Construction du sujet-femme et imaginaire dissident : Largo desolato de Václav Havel - Deret, Anne (Université du Québec à Montréal, 1997)
Keywords: 1900-1999; 1980-1989; IREF; discipline; europe; mémoires/thèses; périodes historiques; régions géographiques; république tchèque; science politique; science politique et droit; théâtre

Les politiques de décriminalisation de la prostitution - Lamarre, Marie-Josée (Université du Québec à Montréal, 1997)
Keywords: IREF; amériques; canada; discipline; droit criminel; droits des femmes*; mémoires/thèses; prostitution; régions géographiques; science politique; science politique et droit; thématiques

Les femmes et le pouvoir municipal au Nouveau-Brunswick - Pitre, Sonia (Université du Québec à Montréal, 1997)
Keywords: IREF; amériques; discipline; droits des femmes*; femmes* politiques; mémoires/thèses; nouveau-brunswick; régions géographiques; science politique; science politique et droit; thématiques

Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; cours; discipline; droit; famille; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; science politique et droit; sciences humaines; thématiques; théologie; violences; violences contre les femmes*

A diplomacy of the oppressed: New directions in international feminism - Ashworth, Georgina (Zed Books, 1995)
Les contributrices abordent les problèmes du mouvement international des femmes, tels que la résolution des conflits; la violence; zones de libre-échange ; l'environnement; culture et identité nationale; santé; les média; droits humains; et l'emploi, en mettant l'accent sur la situation des femmes dans toutes les régions du monde. Destiné aux étudiants en études féministes, en sciences politiques et en études du développement
Keywords: 1900-1999; anthologie; approches et analyses; conflit; coopérative internationale; cours; discipline; fem1000; genre; histoire; histoire et politique; identités LGBTQIA2+; inégalités; militance; mouvements des femmes*; mouvements féministes; premier cycle; périodes historiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques

Démocratie et représentation - Riot-Sarcey, Michèle (Kimé, 1995)
La représentation politique est aujourd’hui en crise : partout en Europe, la légitimité des représentants est contestée, sans pour autant que la démocratie, en son principe, soit mise en cause. A partir de ce constat, des chercheurs des différentes disciplines ont questionné la représentation dans son actualité politique et dans sa formation historique. L’usage de la représentation, la délégation d’autorité qu’elle suppose, la violence qu’elle engendre, la domination qu’elle implique, la pratique démocratique qu’elle présuppose ont été soumis à examen par les intervenants au colloque organisé par le Centre Culturel de l’Albigeois. Les disfonctionnements et les apories d’une démocratie, longtemps considérés comme une donnée perfectible, se révèlent comme un simple produit des règles d’un système exclusif, qui contribuent largement à tenir à l’écart des pouvoirs et des lieux de représentation politiques les femmes comme la grande majorité d’une population, par ailleurs de plus en plus politisée.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; interdisciplinarité; occident; premier cycle; périodes historiques; représentation politique; science politique; science politique et droit; sciences humaines; théories féministes

Defending pornography: free speech, sex, and the fight for women's rights - Strossen, Nadine (Scribner, 1995)
This book examines a key question that has divided feminists for decades: is censoring pornography good or bad for women? The book makes a powerful case that increasing government power to censor sexual expression, beyond the limits that the First Amendment sensibly permits (for example, outlawing child pornography) would do more harm than good for women and others who have traditionally been marginalized due to sex or gender. The book explains how the very anti-porn laws pushed by some feminists have led to the censorship of LGBTQ+ and feminist works, and it examines the startling connections between anti-porn feminists and right-wing fundamentalists. The book lays out the multiple current assaults on sexual expression, which continue to come from across the ideological spectrum. It shows that freedom for such expression remains an essential prerequisite for the equality, safety, and dignity of women and sexual/gender minorities.
Section: 320 p. : ill. ; 22 cm
Keywords: amériques; cours; discipline; droit; droits des femmes*; liberté d'expression; pornographie; premier cycle; régions géographiques; science politique et droit; sex wars; sex1911; thématiques; états-unis

Femmes, action politique et identité - Sève, Micheline de (Cahiers de recherche sociologique, 1994)
Centré sur la différence de genre, le mouvement des femmes serait condamné à l’éclatement à mesure que les femmes échappent à leur cantonnement dans l’appartenance à une catégorie sociale opprimée pour gagner l’espace qu’offre une société démocratique égalitaire à l’expression pluraliste des composantes multiples de leur personnalité publique. Une approche phénoménologique, axée sur la valorisation des expériences de vie et de l’histoire partagées de femmes se réclamant d’une culture civique commune, permet à l’autrice d’espérer dégager une stratégie féministe parallèle fondée sur la prise en compte des positions variées de sujets-femmes en situation pour les rallier autour d’actions politiques à mener en commun.
Keywords: cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; militance; mouvements des femmes*; ressource en ligne; science politique; science politique et droit; thématiques

Une victoire à la Pyrrhus ? : la lutte pour le droit à l’avortement - Lamoureux, Diane (Avortement : pratiques, enjeux, contrôle social, 1993)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; discipline; histoire des femmes*; histoire et politique; justice reproductive; militance; périodes historiques; québec; régions géographiques; science politique; science politique et droit; thématiques

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

La collaboration à travers les différences : quelques réflexions sur les émotions et la pratique politique - Narayan, Uma (Canadian Journal of Women and the Law, 1993)
Uma Narayan tente de clarifier le contenu de la notion féministe de "privilège épistemique des opprimé-es". Elle soutient que le privilege épistémique des "initié-es" opprimé-es concernant leur oppression suscite des problèmes de dialogue et de politique de coalition avec les "non-initié-es" qui eux, ne subissant pas cette oppression, n'arrivent pas à se réconcilier au privilege épistémique des initié-es. Elle analyse concrètement comment les non-initié-es peuvent par inadvertance blesser les initié-es, et elle propose des moyens permettant de minimiser ces problèmes.
Keywords: approches et analyses; discipline; injustices épistémiques; intersectionnalité; inégalités; militance; privilèges; ressource en ligne; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; émotions; épistémologie

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Un genre trouble: le féminisme, la pornographie, la réforme du droit et la thèse de la reproduction de l'ordre social - Lacombe, D. (Déviance et société, 1992)
L'étude de la campagne de criminalisation de la pornographie au Canada, dans les années 1980, pose un défi au savoir conventionnel qui s'est développé, en sociologie et en criminologie, sur la réforme du droit. Ce savoir est l'argumentation selon laquelle les réformes, en dispersant le contrôle social, ne font que légitimer le système sans le modifier fondamentalement. Afin d'éviter l'essentialisme de ce savoir, j'ai utilisé une approche reflexive qui pense la relation entre la réforme du droit et le pouvoir comme à la fois contraignante et facilitante. L'établissement d'un lien entre la pornographie et la déviance sociale n'apparaît pas comme une construction sociale unifiée, mais comme un terrain contesté dans lequel se produisent des rapports de pouvoir complexes, et une multiplicité de stratégies de résistance. C'est dans ce sens que la réforme apparaît comme un mécanisme générateur des pratiques.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; criminologie; discipline; droit; féminisme pop; justice sociale; pornographie; premier cycle; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; thématiques

Feminist hesitations, postmodern exposures - Brown, Wendy (differences, 1991)
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; postmodernisme; science politique; science politique et droit

Demarginalizing the intersection of race and sex: A black feminist critique of antidiscrimination doctrine, feminist theory and antiracist politics - Crenshaw, Kimberle (The University of Chicago Legal Forum, 1989)
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; droit; féminismes noirs; incontournable; intersectionnalité; militance; pol4212; premier cycle; projet charge mentale; racisme; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; états-unis

Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis

Toward a race-conscious pedagogy in legal education - Crenshaw, Kimberle Williams (National Black Law Journal, 1988)
Keywords: afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; féminismes noirs; ressource en ligne; régions géographiques; science politique et droit; états-unis

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach–in which pornography is defined as sex discrimination and therefore a violation of civil rights–would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance–what it is, what it does, what it means, how it works. Answers to the lies about it–lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." –from Pornography and Civil Rights
Section: 142 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

Feminism as critique: On the politics of gender - Benhabib, Seyla; Cornell, Drucilla (University of Minnesota Press, 1987)
Il s'agit d'un remarquable recueil d'essais qui rassemble pour la première fois l'œuvre d'un groupe d'écrivain.e.s bien connu dans la tradition marxiste-féministe. Les essais vont de Marx à Foucault et vont au-delà pour offrir de véritables avancées dans la manière dont la vie sociale et politique peut être reconceptualisée à la lumière de la critique féministe
Keywords: 1900-1999; approches et analyses; cours; cycles supérieurs; discipline; fem9000; féminisme marxiste; genre; identités LGBTQIA2+; inégalités; périodes historiques; science politique; science politique et droit; systèmes d'oppressions; thématiques

Passionate politics: Feminist theory in action - essays, 1968-1986 - Bunch, Charlotte (St. Martin's Griffin, 1987)
Essays discuss feminism, reform, lesbianism, education, the media, and the status of women around the world
Keywords: 1900-1999; amériques; approches et analyses; discipline; féminisme radical; hétérosexisme; lesbianisme; militance; mouvements des femmes*; périodes historiques; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; états-unis

Pour un féminisme libertaire - Sève, Micheline de (Boréal express, 1985)
Une invitation sans réserve à la liberté, qui montre sans équivoque que la cause des femmes est aussi celle des hommes.
Keywords: 1900-1999; amériques; cours; discipline; europe; fem1000; occident; pratiques féministes; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; théories féministes

Le féminisme égalitaire - Castro, Ginette (Radioscopie du féminisme américain, 1984)
Keywords: 1900-1999; amériques; cours; discipline; fem1000; histoire du féminisme; histoire et politique; militance; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; thématiques; états-unis

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Les éditions du remue-ménage, 1983)
Les textes Morgan, R. (1983). La pornographie et le viol : théorie et pratique et Dworkin, A. (1983). Pour les hommes, liberté d’expression. Pour les femmes, silence, s’il vous plaît ont été donné en lecture au corus SEX1911.
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children–The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis

Lesbians in Revolt - Bunch, Charlotte (Lesbianism and the women's movement, 1975)
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; lesbianisme; militance; mouvements des femmes*; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; thématiques; états-unis